2022
DOI: 10.3390/ijerph19073770
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Prolonged Visual Display Terminal Use on Physical and Mental Conditions among Health Care Workers at Tertiary Hospitals, Taiwan

Abstract: This study aimed to examine the effects of prolonged VDT working time on physical and mental health disadvantages among health care workers (HCWs) in tertiary hospitals based on their work characteristics, age, and sex. Included in the study were 945 and 1868 participants in the non-doctor/nurse and doctor/nurse groups, respectively. The questionnaire included VDT usage-related information, the Nordic Musculoskeletal Questionnaire (NMQ), computer vision syndrome (CVS), perceived occupational stress, burnout, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…This study found that the most common complaints of asthenopia subjects were discomfort caused by the brightness of the mobile phone or computer screens, discomfort around the eyes, dryness and soreness of eyes, which was partly supported by our previous findings [2] (ocular complaints and eye dryness were the most common symptoms in asthenopia). Studies showed computer screen exposure was significantly related to asthenopia [35] , and short-wavelength filtering lenses could effectively relieve asthenopia [36] . Exposure to direct glare induced greater development of visual symptoms and discomfort [37] .…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the most common complaints of asthenopia subjects were discomfort caused by the brightness of the mobile phone or computer screens, discomfort around the eyes, dryness and soreness of eyes, which was partly supported by our previous findings [2] (ocular complaints and eye dryness were the most common symptoms in asthenopia). Studies showed computer screen exposure was significantly related to asthenopia [35] , and short-wavelength filtering lenses could effectively relieve asthenopia [36] . Exposure to direct glare induced greater development of visual symptoms and discomfort [37] .…”
Section: Discussionmentioning
confidence: 99%